Abiraterone induces SLCO1B3 expression in prostate cancer via microRNA-579-3p - Roberto H. Barbier (Nature Portfolio, 2021)
Abstract Understanding mechanisms of resistance to abiraterone, one of the primary drugs approved for the treatment of castration resistant prostate cancer, remains a priority. The organic anion polypeptide 1B3 (OATP1B3, encoded by SLCO1B3) transporter has been shown to transport androgens into prostate cancer cells. In this study we observed and investigated the mechanism of induction of SLCO1B3 by abiraterone. Prostate cancer cells (22Rv1, LNCaP, and VCAP) were treated with anti-androgens and assessed for SLCO1B3 expression by qPCR analysis. Abiraterone treatment increased SLCO1B3 expression in 22Rv1 cells in vitro and in the 22Rv1 xenograft model in vivo. MicroRNA profiling of abiraterone-treated 22Rv1 cells was performed using a NanoString nCounter miRNA panel followed by miRNA target prediction. TargetScan and miRanda prediction tools identified hsa-miR-579-3p as binding to the 3′-untranslated region (3′UTR) of the SLCO1B3. Using dual luciferase reporter assays, we verified that hsa-miR-579-3p indeed binds to the SLCO1B3 3′UTR and significantly inhibited SLCO1B3 reporter activity. Treatment with abiraterone significantly downregulated hsa-miR-579-3p, indicating its potential role in upregulating SLCO1B3 expression. In this study, we demonstrated a novel miRNA-mediated mechanism of abiraterone-induced SLCO1B3 expression, a transporter that is also responsible for driving androgen deprivation therapy resistance. Understanding mechanisms of abiraterone resistance mediated via differential miRNA expression will assist in the identification of potential miRNA biomarkers of treatment resistance and the development of future therapeutics.